Impact of urban land on the risks of karst processes in the NPP location area (on the example of Rivne NPP) - Vasiutynska, K.A.; Barbashev, S.V.; Smyk, S.Yu. (Problems of Atomic Science and Technology, 2023)
The aim of the article is to assess the impact of urbanized areas on the risk of developing karst processes in the area of nuclear power plant location and on the safety of the plant (using the example of the Rivne nuclear power plant). Karst features in the area around the Rivne nuclear power plant were visualized using GIS methods. Systematization of karst hazards was carried out with regard to their impact on the structural integrity and safety of the long-term operation of the Rivne nuclear power plant. The impact of urbanized areas on the geological environment was assessed, and a correlation was established between urbanization factors and the activation of karst-suffusion processes. It is shown that urbanization can contribute to the emergence of karst manifestations and, as a result, to threaten to the safety of NNP. Approaches aimed at improving the assessment of karst hazards, monitoring of the main factors of their activation, and managing urbanized areas to increase the safety of nuclear power plants were proposed. Метою статті є оцінка впливу урбанізованих територій на ризик розвитку карстових процесів у районі розташування АЕС і на безпеку АЕС (на прикладі Рівненської АЕС). Візуалізовані карстові особливості в зоні розташування Рівненської АЕС із застосуванням ГІС-методів. Проведено систематизацію карстових небезпек щодо впливів на конструктивну цілісність та безпеку тривалого функціонування Рівненської АЕС. Оцінено впливи урбогенних територій на геологічне середовище, та встановлена кореляція чинників урбанізації та активізації карстово-суфозійних процесів. Показано, що урбанізація може впливати на ініціювання карстопроявів і, як наслідок, поставити під загрозу безпеку АЕС. Запропоновано підходи, які спрямовані на покращення оцінки карстових небезпек, моніторингу основних чинників їх активізації, а також на практику управління урбанізованими територіями для підвищення безпеки атомних електростанцій.